Psicomotricidad y expresión oral en estudiantes de la Institución Educativa N° 818 de nivel inicial Putumayo 2024 - Espinoza Mera, Jelly Zoraida (2024)
The objective of this study was to determine the relationship between psychomotor skills and oral expression in initial level students of Educational Institution No. 818 of Putumayo in the year 2024. A non-experimental design with a quantitative approach and correlational scope was used. The results showed a significant relationship between the variables, with a correlation coefficient of 0.840, indicating a strong and direct relationship. This finding was corroborated by the Student's t value (t=11.309); p-value =0.000). In addition, a relationship was determined between the dimensions of psychomotor skills, such as coordination, language and motor skills, with oral expression in the students evaluated. The study concluded that psychomotor skills directly influence the oral expression ability of children at the initial level.